Training barn owls: a powerful tool in ecological experiments. Issue 3 (1st October 2016) - Subach, Aziz
Abstract : Predators affect prey directly by predation and indirectly by triggering behavioral responses that aim at reducing predation risk. In this paper, I present a method for training an avian predator which can allow separating between its direct and indirect effects on prey in various experimental setups. Barn owls are found to be a valuable tool for empirically testing different hypotheses related to predator-prey interactions, population dynamics, and inter-specific competition, all performed in the field using authentic rodent prey and their natural predators. Barn owls are raised and trained to participate in field experiments using classical conditioning, and are trained either to catch rodents or only to fly above a certain area without making any attempt to attack the prey, simulating solely predation risk. Body mass is a crucial factor in the training procedure, and I thus define five body mass ranges that characterize different behavioral stages in the training of owls. A logistic model is used to calculate and to predict changes in the body mass during the growth and training periods of owls. Finally, I discuss several possible implications of the usage of trained barn owls in empirical studies.